Impact of Toxoplasma gondii Infection on Host Non-coding RNA Responses - Menard, Kayla L.; Haskins, Breanne E.; Denkers, Eric Y. (Frontiers in Cellular and Infection Microbiology, 2019)
As an intracellular microbe, Toxoplasma gondii must establish a highly intimate relationship with its host to ensure success as a parasite. Many studies over the last decade-and-a-half have highlighted how the host reshapes its immunoproteome to survive infection, and conversely how the parasite regulates host responses to ensure persistence. The role of host non-protein-coding RNA during infection is a vast and largely unexplored area of emerging interest. The potential importance of this facet of the host-parasite interaction is underscored by current estimates that as much as 80% of the host genome is transcribed into non-translated RNA. Here, we review the current state of knowledge with respect to two major classes of non-coding RNA, microRNA (miRNA) and long non-coding RNA (lncRNA), in the host response to T. gondii infection. These two classes of regulatory RNA are known to have profound and widespread effects on cell function. However, their impact on infection and immunity is not well-understood, particularly for the response to T. gondii. Nevertheless, numerous miRNAs have been identified that are upregulated by Toxoplasma, and emerging evidence suggests a functional role during infection. While the field of lncRNA is in its infancy, it is already clear that Toxoplasma is also a strong trigger for this class of regulatory RNA. Non-coding RNA responses induced by T. gondii are likely to be major determinants of the host's ability to resist infection and the parasite's ability to establish long-term latency.